Development of the social capital of street vendors in maintaining their existence on land owned by the Ministry of Home Affairs - Ginting, Mathius Pryangga; Anugrahini, Triyanti (Harmoni Sosial: Jurnal Pendidikan IPS, 2023)
The purpose of this study is to describe the social capital development of street vendors on land belonging to the Ministry of Home Affairs in Pondok Labu Village as an effort to maintain their existence. This study used a qualitative approach with a descriptive research type. Data was collected through in-depth interviews with 21 informants who were determined purposively. The results of the study found that on the social capital bonding side, which was based on ethnicity and type of business on the same land, it was found that development began with the existence of kinship relations that invited each other among the families and continued business activities that had existed before and efforts to maintain social relations were carried out by sharing information about market activities and sharing assistance. On the bridging social capital side, seen from the differences in ethnicity, type of business, and relationships among sellers outside the surrounding location, it was found that the initial relationship was formed through interaction by communicating with each other and various contacts to meet customer needs as well as efforts to strengthen socially by sharing assistance and coordinating fulfillment the needs of customer requests. While the social capital linking side is seen from the relationship between street vendors and the owner of authority stems from the existence of an authority relationship that creates norms that have been agreed upon and must be obeyed by every street vendor.